Anticancer activity of Annona species: a systematic review - Corrêa, Patricia Luciana Carriel [UNESP]; Martínez-Vázquez, Mariano; De-la-Cruz-Chacón, Iván; Mimi, Carolina Ovile [UNESP]; Ferreira, Gisela [UNESP] (Springer Nature, 2025)
The genus Annona, which belongs to the Annonaceae family, has several biological activities, including anticancer activity. Cancer is one of the leading causes of death worldwide, requiring investigation of new alternatives to combat it. This systematic review aims to analyze the chemodiversity of plant organs of the genus Annona and their anticancer activity. A systematic search was performed in the Scopus, PubMed and Web of Science databases, using the search terms: “Annona” AND “antitumor OR anticancer OR cytotoxic OR antitumoral OR cancer”. The review only included studies that mentioned the compounds present in extracts of Annona species that have shown activity against cancer cells. Of the 166 species of the genus Annona, 29 have been studied for their anticancer activity in their extracts or compounds. Specialized metabolites of Annona species with anticancer activity include alkaloids, acetogenins, terpenes, flavonoids, coumarins, cyclopeptides and saponins, with distinct mechanisms of action. The most studied plant organs are leaves and seeds. Acetogenins isolated from seeds are the metabolites most evaluated against several cancer cell lines, reflecting the interest in their high inhibitory potential. The chemodiversity of plant organs of Annona species has high cytotoxic potential, especially with the presence of acetogenins.Graphical abstract